Assessing habitat fragmentation of the KwaZulu-Natal Sandstone Sourveld, a threatened ecosystem - Naicker, Rowan; Rouget, Mathieu; Mutanga, Onisimo (African Biodiversity & Conservation, 2016)
Background: The KwaZulu-Natal Sandstone Sourveld (KZN SS) is a grassland ecosystem categorised as endangered by the terms of the National Environmental Management: Biodiversity Act (Act 10 of 2004). Pressure from urbanisation has led to the remaining areas of the KZN SS being physically fragmented, causing low connectivity levels which have diminished the biological persistence of this ecosystem. Objectives: This study aimed to quantify the overall level of habitat fragmentation of the KZN SS and determine the level of connectivity within the ecosystem, and patches of the KZN SS occurring in the eThekwini Municipal area. Using graph theory, we compared the effectiveness of broad-scale and fine-scale data sets in quantifying habitat fragmentation. Methods: The Conefor Sensinode software, which employs the bases of graph theory, was chosen to aid in assessing fragmentation levels. The integral index of connectivity (IIC) (values range from 0 to 1, with 1 highlighting optimal connectivity) was chosen as the best index to determine landscape connectivity. Results: The KZN SS was shown to be highly fragmented, especially at dispersal distances less than 500 m. This resulted in very low connectivity levels, with the highest IIC value recorded at 0.0063. Moreover, the use of either fine-scale or broad-scale data to measure connectivity differed substantially at 1000 m. Conclusion: Broad-scale data were shown to overestimate habitat fragmentation and underestimate landscape connectivity. A more apt description of KZN SS connectivity levels was realised with fine-scale data. This study recommends that crucial KZN SS patches be prioritised to safeguard this endangered ecosystem.